Pengaruh Gaya Kepemimpinan Transformasional Terhadap Perilaku Inovatif Karyawan Dan Kinerja Umkm Kecamatan Kraton Yogyakarta - Noor Kurniyati, Nany (Kajian Ekonomi dan Bisnis, 2018)
This study aims to analyze the influence of dimensions at transformational leadership style on employees’ innovative behavior and UMKM performance engaged in creative industries in Kraton District of Yogyakarta. The study was conducted on UMKM included in the creative industries in Kraton District of Yogyakarta. This research is a quantitative research in which the data analysis refers more to numbers that will be analyzed by statistical analysis. The data was collected through questionnaires and documentation. The research used validity and reliability testing for the test research instruments. the data analysis used are descriptive analysis, inferential analysis (multiple linear regression and simple linear regression), coefficient determination test (R2) and significance test of individual parameters (t test). The results show that 1) the dimensions of idealized influence affect innovative behavior. 2) The dimensions of inspirational motivation affect innovative behavior. 3) The dimensions of intellectual stimulation affect innovative behavior. 4) Individual consideration dimensions affect individual innovative behavior. 5) The dimensions of idealized influence affect the UMKM performance . 6) The dimensions of inspirational motivation affect the UMKM performance. 7) The dimensions of intellectual stimulation affect the UMKM performance . 8) The individual consideration dimensions affect theUMKM performance . 9) There are simultaneously effects of dimension influence, idealized influence, inspirational motivation, intellectual stimulation, and individual consideration on innovative behavior. 10) There are simultaneously effects of dimension influence, idealized influence, inspirational motivation, intellectual stimulation, and individual consideration on the UMKM performance . 11) The employees’ innovative behaviors affect the UMKM performance.